PENGGUNAAN SUPER DECISION SOFTWARE DALAM MENENTUKAN DOSEN PENGAJAR MATAKULIAH DI PERGURUAN TINGGI - Deppi Linda (Jurnal Informatika, 2013)
To be able to compete with other universities, one of the efforts is to improve the service quality to students by giving right lecturer on the right subjects. This research is referring to priority of lecturer in private university by doing assessment lecturer performance for each semester to determine quality and competence of lecturer finally will give the affect in determining subjects will be taught. The obstacle is such as there is no information system to determine lecturers which are suitable of education background. This research produced a model that support a decision in determining lecturer with the best performance will be teaching certain subjects in each period. In this research, use super decision software to determine lecturers on the right subjects. Key word: decision support, super decision, assessment of lecturer